Drone orthomosaic and DEM of the Nuusaq archaeological site in NW Greenland - Carlson, Daniel; Walsh, Matthew; Thomsen, Steffen; Tejsner, Pelle (Zenodo, 2023)
This dataset consists of a digital elevation model (DEM) and an orthomosaic of the Nuusaq archaeological site, located on the Nuussuaq Peninsula in NW Greenland. The DEM and orthomosaic were produced from 2143 aerial images that were acquired by a DJI Phantom 3 drone. The images were processed using Agisoft Metashape Professional (version 1.7.1) following protocols established by the United States Geological Survey (USGS) for drone surveys of coastal regions (Over et al., 2021). The drone survey of the Nuusaq site was conducted as part of the Vaigat Iceberg-Microbial Oil Degradation and Archaeological Heritage Investigation (VIMOA) project, which was funded by the Danish Centre for Marine Research and supported by the Arctic Research Centre at Aarhus University, in affiliation with the National Museum of Denmark, the Greenland Institute of Natural Resources, and The Greenland National Museum and Archives in Nuuk. Archaeological permits for the survey were obtained in advance from the Greenland National Museum and Archives in Nuuk. Walsh et al. (2020) provide an overview of the archaeological surveys conducted during the VIMOA project. Over et al. (2021) Processing Coastal Imagery With Agisoft Metashape Professional Edition, Version 1.6—Structure From Motion Workflow Documentation. USGS Open File Report 2021-1039. doi:10.3133/ofr20211039. https://pubs.er.usgs.gov/publication/ofr20211039 Walsh et al. (2020) The VIMOA project and archaeological heritage in the Nuussuaq Peninsula of north-west Greenland. Antiquity 94:e6 doi:10.15184/aqy.2019.230